2005
DOI: 10.1002/ptr.1657
|View full text |Cite
|
Sign up to set email alerts
|

Altered dendritic arborization of amygdala neurons in young adult rats orally intubated with Clitorea ternatea aqueous root extract

Abstract: Young adult (60 day old) Wistar rats of either sex were orally intubated with 50 mg/kg body weight and 100 mg/kg body weight of aqueous root extract of Clitoria ternatea (CTR) for 30 days, along with age-matched saline controls. These rats were then subjected to passive avoidance tests and the results from these studies showed a significant increase in passive avoidance learning and retention. Subsequent to the passive avoidance tests, these rats were killed by decapitation. The amygdala was processed for Golg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…Only secondary dendrites that clearly arose from a single branch point shared by at least two other secondary dendrites were classified as excess secondary dendrites. The formation of multiple dendrites from a single branch point is a normal branching pattern that has been shown to occur in vivo (Fan et al, 2005;Rai et al, 2005). To reduce the possibility of researcher bias, the investigator performing the above procedure was always blinded to the experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Only secondary dendrites that clearly arose from a single branch point shared by at least two other secondary dendrites were classified as excess secondary dendrites. The formation of multiple dendrites from a single branch point is a normal branching pattern that has been shown to occur in vivo (Fan et al, 2005;Rai et al, 2005). To reduce the possibility of researcher bias, the investigator performing the above procedure was always blinded to the experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Clitoria ternatea (commonly called Shankapushpi) aqueous root extract treatment of rats has shown: (1) improved learning and memory (including passive avoidance learning) (Rai et al 2001); (2) increased dendritic arborization of CA3 neurons of the hippocampus (Rai et al 2000); (3) increased acetylcholine content of the hippocampus (Rai et al 2002); and (4) increased dendritic arborization of amygdala neurons (Rai et al 2005). A few other herbal extracts have also been reported to show similar effects.…”
Section: Discussionmentioning
confidence: 98%
“…Advanced neuroscience research has shown that the learning process is associated with alterations in the dendritic morphology of the hippocampal (Mahajan and Desiraju 1988;Rao et al 1993;Bharathi et al 1999;Bindu et al 2007) and amygdaloid (Vyas et al 2002;Rai et al 2005) neurons. Though there are reports showing that BM improves learning and memory in rats, there is no direct experimental evidence to show the correlation of the action of this plant extract on behavior, especially learning and memory, with histological changes in brain.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The anthocyanins and delphinidin glucoside present in blue flowered variety [23]. Pharmacologically it is reported for improved cognitive abilities, learning and memory, neuronal degenerative disorders [24][25][26][27]; nootropic and anticonvulsant activities [28]; antimicrobial and insecticidal [29][30]; antipyretic, analgesic, anti-inflammatory [31][32]; antioxidant, hepatoprotective, antidiabetic, [33] and platelet aggregation inhibitory [34] activities. The detailed pharmacognostic study of two varieties of C. ternatea viz.…”
Section: Introductionmentioning
confidence: 99%